Diagnosis dan Penatalaksanaan Trigeminal Neuralgia - Zefanya, Ezekial; Berawi, Khairun Nisa; Septiani, Linda; Wardani, Dyah Wulan Sumekar Rengganis (Medula, 2025)
Trigeminal Neuralgia (TN) is a sudden pain in the facial area, short duration for about one second to two minutes, being-stabbed feels like, and occurs repeatedly in one or more branches of the trigeminal nerve. Type 1 (one) as intermittent pain and type 2 (two) as constant pain with different clinical, pathological, and prognostic complaints. The causes of Trigeminal Neuralgia involve peripheral pathology in the roots (compression or traction), brainstem dysfunction, basal ganglia, and cortical pain modulation mechanisms, but the most common is due to neurovascular factors. The diagnosis of Trigeminal Neuralgia is basically clinical, to rule out secondary causes, detect pathological changes in the affected roots and neurovascular compression (NPC), Magnetic Resonance Imaging (MRI) may be used. The choice of first-line drug therapy is carbamazepine, and for the second line patient may use oxcarbazepine, baclofen, lamotrigine, phenytoin, and topiramate. Microvascular decompression (MVD) is the surgical treatment of choice for TN that is resistant to medical management. Patients with significant medical comorbidities, without neurovascular compression and multiple sclerosis are generally advised to undergo gamma knife radiosurgery, percutaneous balloon compression, glycerol rhizotomy, and radiofrequency thermocoagulation procedures. The most effective medical therapy is with carbamazepine with a reported reduction in facial pain after taking it as much as 47 percent. For patients who do not respond to medical treatment, microvascular decompression surgery is performed with an effectiveness rate in patients as much as 90 percent.